Dirty Bertie Zombie - MacDonald, Alan.; Roberts, David (London : Stripes Publishing, 2013)
Calling all Dirty Bertie fans! Dirty Bertie - the boy with nose-pickingly disgusting habits - is back for another helping of comic chaos! More disgusting than ever, with crazier plans and increasingly madcap schemes, Bertie continues to delight his legions of fans who revel in his revolting ways. Join Bertie in Zombie!
3-6.
Turkish.
Keywords: Behavior -- Fiction; Zombie -- Fiction